Processing and characterisation of particulate reinforced aluminium -11.8% silicon matrix composite - M., Sayuti; S., Suraya; Sulaiman, Shamsuddin; Baharudin, B. T. Hang Tuah; Mohd Ariffin, Mohd Khairol Anuar (Universiti Putra Malaysia, 2010)
This paper describes and discusses the processing and characterization of titanium carbide particulate reinforced aluminium-silicon alloy matrix composite. In this regard, titanium carbide particulate reinforced LM6 alloy matrix composites were fabricated by carbon dioxide sand molding process with different particulate weight fraction. Tensile tests and scanning electron microscopic studies were conducted to determine the maximum load, tensile strength, modulus of elasticity and fracture surface analysis have been performed to characterize the morphological aspects of the test samples after tensile testing. Hardness values are measured for the quartz particulate reinforced LM6 alloy composites and it has been found that it gradually increases with increased addition of the reinforcement phase. The tensile strength of the composites increases with the increase in addition of quartz particulate.